Towards a European health information system: The BRIDGE Health, InfAct and PHIRI projects - Martin Thißen; Angela Fehr; Aline Anton; Stefanie Seeling; Thomas Ziese (Journal of Health Monitoring)
Background: National health systems in Europe are facing similar challenges – demographic change, a rising burden of disease due to chronic non-communicable diseases, and health inequalities. Comparable health data and knowledge sharing between countries are therefore an important basis for policy decision-making. However, health information in the European Union (EU) is fragmented and approaches to establishing a comprehensive system are largely project-based. Methods: This contribution describes the European projects BRIDGE Health (2015 – 2017), InfAct (Information for Action, 2018 – 2021) and PHIRI (Population Health Information Research Infrastructure, 2020 – 2023), which aimed at developing a sustainable health information infrastructure. Results: The projects, which build on one another, laid the groundwork for an EU-wide health information system. For example, a health information portal was established, a federated research infrastructure was implemented, handouts were created and training on capacity building was provided. Conclusions: An integrated EU-wide health information system is an important basis for policy decision-making and a prerequisite for a rapid and coordinated response to health crises. A sustainable structure or institution with a mandate for non-communicable diseases (NCD) and their determinants at the EU level would be desirable.